2018
DOI: 10.1007/s00217-018-3169-2
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the antimicrobial activity of bacteriocin-like inhibitory substances of enological importance produced by Oenococcus oeni isolated from wine

Abstract: We experimentally determined that bacteriocin-like inhibitory substances synthetized by Oenococcus oeni may act as a natural preservative and may thus be of importance for the wine industry. An O. oeni strain isolated from wine was tested for antimicrobial activity against ten indicator lactic acid wine spoilage bacteria of enological origin from the genera Lactobacillus, Leuconostoc, and Pediococcus. A strong competition effect of O. oeni against all the tested indicator bacteria was noted. The antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Moreover, whereas other crude BLIS fractions showed a significant decrease in activity, only the crude BLIS of S. variabilis SCA-11 and SCA-5 completely lost their activity following pepsin treatment. These findings are consistent with those of Lasik-Kurdyś and Sip [ 35 ], who reported that BLIS produced by Oenococcus oeni loses its activity after exposure to pronase E, proteinase-K, trypsin, pepsin, and α -chymotrypsin. Moračanin et al [ 36 ] also found that the bacteriocin produced by Leuconostoc mesenteroides loses its antilisteria activity after exposure to pepsin, papain, and proteinase-K.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, whereas other crude BLIS fractions showed a significant decrease in activity, only the crude BLIS of S. variabilis SCA-11 and SCA-5 completely lost their activity following pepsin treatment. These findings are consistent with those of Lasik-Kurdyś and Sip [ 35 ], who reported that BLIS produced by Oenococcus oeni loses its activity after exposure to pronase E, proteinase-K, trypsin, pepsin, and α -chymotrypsin. Moračanin et al [ 36 ] also found that the bacteriocin produced by Leuconostoc mesenteroides loses its antilisteria activity after exposure to pepsin, papain, and proteinase-K.…”
Section: Resultssupporting
confidence: 92%
“…The stability of BLIS-GF in this study was consistent with the study of Hernandez-Saldana et al [ 11 ], in which BLIS produced by S. nigrescens was able to maintain almost half its activity at 120 °C and in the pH range of 3.0–10.0. Stability to high temperatures and pH is thought to be caused by several factors such as secondary structure, thermostable amino acid content, and changes in charge due to the influence of isoelectric point [ 31 , 32 ]. Considering that most food products have a neutral to acidic pH and are processed using a heat process [ 33 ], this study showed the potential for use in food preservation processes.…”
Section: Resultsmentioning
confidence: 99%